2020
DOI: 10.1007/s12594-020-1463-7
|View full text |Cite
|
Sign up to set email alerts
|

Rare Metal (RM) and Rare Earth Element (REE) Resources: World Scenario with Special Reference to India

Abstract: The RM (Li, Be, Ti, Zr, Nb, Ta, Th and U) and REE (Light Rare Earths and Heavy Rare Earths including Yttrium) are strategic and critical for sustaining a variety of industries such as nuclear, defence, information technology (IT) and green energy options (wind, solar, electric vehicles and others). The 2010 ‘Rare Earth’ crisis of the world, following China’s monopoly with over 80% share and export restrictions in the REE market, led to an exploration boom for REE all over the world including India. This led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…REE and the alloys that contain them are used in a variety of high-tech applications, such as the national defense and satellite systems, radar systems, wind turbines, electric vehicles, rechargeable batteries, laser crystals and robots. The 2010 'Rare Earth' crisis of the world, following China's monopoly with over 80% share and export restrictions in the REE market, led to an exploration boom for REE all over the world, including India (Krishnamurthy, 2020).…”
Section: Occurrence In Different Geological Systems Mineralogy and De...mentioning
confidence: 99%
“…REE and the alloys that contain them are used in a variety of high-tech applications, such as the national defense and satellite systems, radar systems, wind turbines, electric vehicles, rechargeable batteries, laser crystals and robots. The 2010 'Rare Earth' crisis of the world, following China's monopoly with over 80% share and export restrictions in the REE market, led to an exploration boom for REE all over the world, including India (Krishnamurthy, 2020).…”
Section: Occurrence In Different Geological Systems Mineralogy and De...mentioning
confidence: 99%
“…6,7 According to the 2023 reports, India is the world's sixth-largest producer of rare earths with an estimated production of 2900 metric tons of rare earth oxide equivalent. 8 Still there is a wide gap between the availability of existing REE resources and demand for high-tech applications. 9 In view of the increasing demand for REEs and other rare metals, there is an urgent need to explore economically viable new mineral REE deposits and investigate possible strategies to recover them in order to ensure indigenous supply of these rare metals.…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al believed that there have been many studies on the catalytic and surface performance of alkali metal, alkaline earth metal, and other metal oxides, but rare earth oxides have received relatively little attention [ 4 ]. Krishnamurthy presented and explained the geochemical characteristics, classification, and distribution of rare earth elements in sedimentary rocks [ 5 ]. Xiao investigated the effect of rare earth elements on the compressive ductility of ferromagnetic shape memory alloys and found that rare Earth elements can significantly improve the material's compressive ductility [ 6 ].…”
Section: Introductionmentioning
confidence: 99%